Organizational performance of the Provincial Engineers Office - Lucero, Gracianito L.
The study sought to diagnose the organizational structure, examine operating procedures, personnel practices and communication flow, and identify problem areas in the operations of the Provincial Engineers Office. It also sought to determine the efficiency, effectiveness, and responsiveness of the office as perceived by the community. Thirty-nine employees of the Provincial Engineers Office and ten key respondents from the community were the subjects of the study. Utilizing descriptive survey method, the data were gathered through a multiple choice format questionnaire, personal interview with key informants in the barangay, and use of secondary data. The findings revealed that majority of employees perceived the organization to be adequately staffed, with activities and transactions flowing fairly smooth, and information flowing mostly from top management down to the rank and file. Standard operating procedures are well- entrenched in the organization and are clearly well-understood by all. Political orientation in recruitment, selection, and promotion is perceived as the major problem in staffing. The organizational activities are characterized by a high degree of task interdependence which necessitates a high degree of coordination between divisions and sections. Yet the research findings revealed only moderate cooperative teamwork and person-to-person relationship in the organization. In the community level, majority of people perceive increased productivity and improved living conditions as among the benefits brought by infrastructure. Still, majority of the people felt the delivery of infrastructure services is very slow and with relatively little effectiveness. In the light of the findings presented. The Provincial Engineers Office should undertake trainings to enhance cooperation and coordination to improve organizational performance. A review of internal systems is recommended with the end view of evolving structural adjustments to the existing organizational model.